Calycopterin, a major flavonoid from Marcetia latifolia, modulates virulence-related traits in Pseudomonas aeruginosa. (July 2020) - Froes, Thamires Quadros; Nicastro, Gianlucca Gonçalves; de Oliveira Pereira, Thays; de Oliveira Carneiro, Kelli; Alves Reis, Isabella Mary; Conceição, Rodrigo Souza; Branco, Alexsandro; Ifa, Demian Rocha; Baldini, Regina Lúcia; Castilho, Marcelo Santos
Abstract: Although bacterial resistance is a worldwide growing concern, the development of bacteriostatic and bactericidal drugs has been decreasing in the last decade. Compounds that modulate the microorganism virulence, without killing it, have been considered promising alternatives to combat bacterial infections. However, most signaling pathways that regulate virulence are complex and not completely understood. The rich chemical diversity of natural products offers a good starting point to identify key compounds that shed some light on this matter. Therefore, we investigated the role of Marcetia latifolia ethanolic extract, as well as its major constituent, calycopterin (5, 4'-dihydroxy-3, 6, 7, 8-tetramethoxylflavone), in the regulation of virulence-related phenotypes of Pseudomonas aeruginosa . Our results show that calycopterin inhibits pyocyanin production (EC50 = 32 μM), reduces motility and increases biofilm formation in a dose-dependent manner. Such biological profile suggests that calycopterin modulates targets that may act upstream the quorum sensing regulators and points to its utility as a chemical probe to further investigate P. aeruginosa transition from planktonic to sessile lifestyle. Highlights: Marcetia latifolia ethanolic extract inhibits pyocyanin production in P. aeruginosa . Calycopterin is the major constituent of the ethanolic extract of Marcetia latifolia . Calycopterin reduces P. aeruginosa motility and increases biofilm formation Calycopterin mechanism of action is compatible with modulation of c-di-GMP-related traits.